Co-decorated tellurium nanotubes for energy storage applications - Bhol, Prangya; Swain, Swarnalata; Jena, Satyaranjan; Bhatte, Kushal; Rout, Chandra Sekhar; Saxena, Manav; Jadhav, Arvind H.; Samal, Akshaya K. (ACS Applied Nano Materials, 2021)
This paper explicitly discusses the synthesis of Co-decorated Te nanotubes (NTs) using Te NTs as the sacrificial template and the evaluation of their electrochemical performance. First, one-dimensional (1D) Te NTs were synthesized and characterized by spectroscopic and microscopic tools such as UV-visible spectroscopy, X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy, field-emission scanning electron microscopy, high-resolution transmission electron microscopy, and energy-dispersive X-ray spectroscopy analyses. The as-prepared hexagonal Te NTs (h-Te NTs) possess diameters of about 35 +/- 5 nm and lengths of about 500 +/- 50 nm and were used for the synthesis of Co-decorated Te NTs. The 1D nanostructure with excellent conductivity enables the material to show excellent electrochemical performance. The asymmetric assembly of the CoTe-2//AC electrode material displayed a high specific capacitance of 147 F g(-1) (specific capacity, 162 C g(-1) at a current density of 2 A g(-1) in 4 M KOH electrolyte. In addition to that, the assembly of CoTe-2//AC achieved an excellent energy density of 51.1 W h kg(-1) at a power density of 2294 W kg(-1) and confirmed the as-synthesized Co-decorated Te NTs to be an excellent electrode material.
Keywords: cobalt; nanotubes; pseudocapacitors; surfactant; Tellurium; template

Shape-controlled MoO3/MnO x nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs - Singh, Nittan; Putla, Suresh Babu; Pratap Singh, Chandrodai; Kalbande, Pavan Narayan; Choudhary, Priyanka; Krishnamurty, Sailaja; Krishnan, Venkata; Bhatte, Kushal; Sudarsanam, Putla (ACS Applied Nano Materials, 2023)
We have developed a highly effective shape-controlled MoO3/MnOx nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs at room temperature without any external oxidant. Electron microscopy images reveal that the MnOx material contains rod-shaped particles (length: 500-1000 nm and width: 150-200 nm) and the MoO3 species are uniformly dispersed in the MoO3/MnOx material. The MoO3/MnOx nanocatalyst calcined at 500 degrees C (MoO3/MnOx-5) contains abundant strong acid sites and an optimum ratio of Mn4+/Mn3+, which are responsible for the C-N cross-coupling reaction between 2-phenylethylamine and o-phenylenediamine, giving higher yields (>96%) of 2-phenylquinoxaline at mild conditions. The broad scope of this catalytic strategy at room temperature and without an external oxidant was confirmed by achieving >90% yields of functional 2-phenylquinoxalines from C-N cross-coupling of various o-phenylenediamines and 2-phenylethylamines. The outstanding reusability efficiency of the MoO3/MnOx-5 nanocatalyst up to five cycles without the need for a regeneration step as well as the effective scalability highlighted the practicability of the MoO3/MnOx-based catalytic protocol for carbon-heteroatom coupling reactions at room temperature and without an external oxidant. Using computational studies, the possible reasons for the selective synthesis of 2-phenylquinoxaline over the MoO3/MnOx-5 nanocatalyst were elucidated.
Keywords: cascade C-N cross-coupling; DFT studies; room temperature andopen air; shape-controlled MoO3/MnOx nanocatalyst; structure-activity correlation

New insights into the composition and catalytic performance of VOx-Ga/γ-Al2O3 for the oxidative dehydrogenation of propane to propene - Kandasamy, Prabu; Gawali, Sheetal; Venugopalan, Aswathy Thareparambil; Manikandan, Marimuthu; Mekala, Siva Prasad; Shelke, Ankita; Ajithkumar, Thalasseril G.; Bhatte, Kushal; Raja, Thirumalaiswamy (New Journal of Chemistry, 2024)
Oxidative dehydrogenation (ODH) of propane is a promising alternative route for propene production. In this work, we developed a series of vanadium and gallium oxides supported on gamma-Al2O3 catalysts by an incipient wetness impregnation method. Among the employed catalysts, the VGA-2 showed superior catalytic activity, and the catalyst was demonstrated for longevity in ODH of propane with a stable activity using a continuous flow fixed bed reactor at 400 degrees C. H-2-TPR and UV-visible spectra showed the presence of highly dispersed monomeric VOx species with tetrahedral coordination geometry, which influences product selectivity. The characterization results also conferred that the redox nature of vanadium (V5+ and V4+) oxide and higher V5+ content on the surface of the VGA-2 catalysts are more favourable for C-H activation. In addition, the pyridine-FTIR and Ga-71 solid-state NMR studies further substantiated the presence of Lewis acid sites and tetrahedrally coordinated Ga3+Ox species that are highly responsible for the ODHP activity, respectively. Furthermore, in situ-DRIFTS studies conferred that the propane adsorption at ambient temperature showed the formation of intermediate propoxide species with the evolution of sigma-bonds and with further increase in the temperature to 325 degrees C; the stretching vibrations of the =C-H and -C-H bonds in the propylene molecule were observed. The spent catalysts were also analyzed by thermogravimetric analysis, where the optimized catalyst (VGA-2) showed the least coke deposition.

Temperature-controlled hydrothermal synthesis of α-MnO2 nanorods for catalytic oxidation of cyclohexanone - Jha, Ratnesh Kumar; Manikandan, Marimuthu; Prabu, Marimuthu; Vineeth, Nidhi R.; Dharmalingam, Praveen; Archana, Ramakrishnan; Harsha, Murudappa; Shankar, Sonu Ram; Bhatte, Kushal; Raja, Thirumalaiswamy (CHEMPLUSCHEM, 2024)
Keywords: Adipic Acid; conversion; MANGANESE OXIDES

Additive-free, selective synthesis of N-heteroaromatics using morphology-engineered hollow CeO2 nanocatalyst - Singh, Nittan; Swapna, Bhattu; Balu, Alina Mariana; Bhatte, Kushal; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2025)
We developed a highly efficient, shape-controlled CeO2 nanocatalyst for synthesizing N-heteroaromatics via an aerobic dehydrogenation approach, operating at mild reaction conditions without needing toxic acid/base additives. Different morphologies of CeO2, namely, hollow nanospheres, nanorods, and irregularly shaped nanoparticles, were synthesized, as confirmed by electron microscopy analysis. The CeO2 hollow nanosphere catalyst (CeO2-HNS) exhibited unique features, such as abundant acid-base sites, larger-sized voids, and surface oxygen vacancies. These characteristics are found to be crucial for the additive-free oxidative dehydrogenation of saturated N-heterocycles over the CeO2-HNS catalyst, resulting in 98% conversion of 1,2,3,4-tetrahydroquinoline with 100% quinoline product selectivity. The versatility of this approach was further demonstrated by the successful aerobic dehydrogenation of a broad range of saturated N-heterocycles, affording N-heteroaromatics in good to excellent yields. Furthermore, the CeO2-HNS nanocatalyst showed exceptional reusability over six cycles without requiring a regeneration step, such as high-temperature calcination treatment. The structural and morphological stability of the CeO2-HNS catalyst, along with reaction scalability and favorable green chemistry metrics, emphasized the practical viability of the CeO2-HNS catalyst for industrial applications.
Keywords: acid-base and defect sites; additive-free aerobicdehydrogenation; CeO2 hollow nanosphere catalyst; N-heteroaromatics; reusability and scalability